2018
DOI: 10.1111/psyp.13078
|View full text |Cite
|
Sign up to set email alerts
|

Detecting violation in abstract pitch patterns with mismatch negativity

Abstract: The human brain automatically extracts regularities embedded in environmental auditory events. This study investigated the extraction of abstract patterns by measuring mismatch negativity (MMN). Participants watched a silent subtitled movie and ignored a sequence of auditory events comprising frequent standards and rare deviants presented in the background. Tone triplets with varying pitch (first-order property) served as the auditory events. The pitch intervals (interval 1 and interval 2) between the tones in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Specifically, TMS on the IFC 80 ms after stimuli onset was applied at the first 2 or 5 positions of standard trains with different train lengths, while the MMN responses to the deviants presented after the standard trains were recorded. Previous studies found MMN response to the deviant when the deviant was preceded by at least 2 standards [29][30][31][32][33], and increase in MMN amplitude with longer standard trains [34]. These results indicate the importance of accumulating information from the standards for eliciting the MMN.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 54%
“…Specifically, TMS on the IFC 80 ms after stimuli onset was applied at the first 2 or 5 positions of standard trains with different train lengths, while the MMN responses to the deviants presented after the standard trains were recorded. Previous studies found MMN response to the deviant when the deviant was preceded by at least 2 standards [29][30][31][32][33], and increase in MMN amplitude with longer standard trains [34]. These results indicate the importance of accumulating information from the standards for eliciting the MMN.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 54%
“…The interevent interval is equivalent to the intertrial interval as each trial was consisted of one auditory event. Previous studies (Bidelman & Chung, ; Denham, Gyimesi, Stefanics, & Winkler, ; Mittag, Takegata, & Winkler, ; Sable et al, ; Sable, Gratton, & Fabiani, ; Sussman, Gomes, Nousak, Ritter, & Vaughan, ; Xiao et al, ) demonstrated perceptual grouping of tones with similar spectral and temporal properties.…”
Section: Methodsmentioning
confidence: 92%
“…While the absolute pitches of the tones (i.e., a physical feature) varied among the events, the regularity of the standard events could only be established by the relative pitch difference between the first and second tone (i.e., an abstract feature), but not by the absolute pitches of the tones. The regularity or prediction violation account of preattentive change detection was further demonstrated by MMNs to the violation of an abstract regularity pattern established not only by a constant abstract relationship between physical features, but also by a constant abstract relationship between abstract features, among the standard events (Xiao et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations